Hubungan antara aspek demografis dan preferensi minuman cokelat instan di wilayah perbatasan: The relationship between demographic aspects and instant chocolate drink preferences in border areas - Akbar, Dzifiar Yasykuri; Adawiyah, Dede Robiatul; Hunaefi, Dase (TEKNOLOGI PANGAN : Media Informasi dan Komunikasi Ilmiah Teknologi Pertanian, 2025)
The high dependence of Indonesian border communities in Batam and Pontianak on imported products is influenced by the perception that foreign products are of better quality, and supported by easy geographical access. This study aims to analyze the relationship between demographic factors and consumer preferences for instant chocolate powdered drinks, in the context of changing border policies directed at becoming the gateway to the national economy. The research was conducted with a quantitative approach through a survey of 200 respondents who were selected purposively with the distribution of quotas per region. The variables analyzed included demographic factors (gender, age, marital status, education level, and type of occupation) as well as product attributes (color, aroma, taste, and texture), using the chi-square test to look at the relationships between variables. The results of the study show a significant relationship between demographic characteristics and consumer preferences. Preference patterns also show differences between regions: consumers in Pontianak tend to choose local products for price and quality reasons, while in Batam, preferences are more influenced by brand information and product image. The organoleptic test revealed that in the blind test, consumers objectively judge the product based on sensory attributes, while in the unblind test, preferences are influenced by the brand as well as demographic factors such as education and employment. These findings confirm the complexity of factors affecting the competitiveness of local products in border areas, as well as the importance of marketing strategies based on demographic segmentation and sensory quality improvement to reduce dependence on imported products.